ANALISIS FAKTOR YANG MEMPENGARUHI RETURN SAHAM PADA BANK UMUM YANG TERDAFTAR DI BURSA EFEK INDONESIA - Mulia Andirfa; Eka Chyntia; Iva Septarina; Maryana (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2021)
This study aims to analyze the effect of ROE, CAR, NPL, BOPO, and DER simultaneously on stock returns in commercial banks listed on the Indonesia Stock Exchange. The data used in this study are secondary data in the form of financial reports at PT. Bank Rakyat Indonesi Tbk, PT. Bank Negara Indonesia Tbk, PT. Bank Mandiri Tbk, PT. Bank Central Asia Tbk, and PT. Bank Mega Tbk. from 2014-2019. The data analysis method used is panel data regression analysis, namely the Fixed Effect Model (FEM). The results showed that: ROE theoretically and statistically affect stock returns in commercial banks listed on the Indonesia Stock Exchange. CAR is theoretically and statistically insignificant to stock returns in Commercial Banks listed on the Indonesia Stock Exchange. BOPO has a theoretical effect but does not have a statistical and significant effect on stock returns in commercial banks listed on the Indonesia Stock Exchange. NPL and DER have no effect on stock returns in Commercial Banks listed on the Indonesia Stock Exchange. ROE, CAR, NPL, BOPO and DER simultaneously have a positive effect on stock returns in) Commercial Banks listed on the Indonesia Stock Exchange. ROE, CAR, NPL, BOPO and DER have the ability to explain their effect on stock returns in Commercial Banks listed on the Indonesia Stock Exchange of 44.09%. The remaining 55.01% is influenced by other variables outside this research model.